2018
DOI: 10.1007/s00330-018-5445-8
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body MRI for staging and interim response monitoring in paediatric and adolescent Hodgkin’s lymphoma: a comparison with multi-modality reference standard including 18F-FDG-PET-CT

Abstract: • This prospective single-centre study showed discordance for full patient staging of 44% between WB-MRI and a multi-modality reference standard in paediatric and adolescent Hodgkin's lymphoma. • WB-MRI underestimates interim disease response in paediatric and adolescent Hodgkin's lymphoma. • WB-MRI shows promise in paediatric and adolescent Hodgkin's lymphoma but currently cannot replace conventional staging pathways including F-FDG-PET-CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 34 publications
(55 reference statements)
3
44
0
3
Order By: Relevance
“…Size changes were also recorded although at a less marked extent between responding and nonresponding lesions . Latifoltojar et al recently confirmed the value of WB‐MRI for the assessment of both nodal and extranodal involvement in pediatric HL patients . However, they stressed that disease response might have been underestimated by WB‐MRI in extranodal sites, making questionable the use of this modality in place of standard examinations, namely, 18 F‐FDG‐PET/CT.…”
Section: Hodgkin Lymphomasmentioning
confidence: 99%
“…Size changes were also recorded although at a less marked extent between responding and nonresponding lesions . Latifoltojar et al recently confirmed the value of WB‐MRI for the assessment of both nodal and extranodal involvement in pediatric HL patients . However, they stressed that disease response might have been underestimated by WB‐MRI in extranodal sites, making questionable the use of this modality in place of standard examinations, namely, 18 F‐FDG‐PET/CT.…”
Section: Hodgkin Lymphomasmentioning
confidence: 99%
“…Whole-body magnetic resonance imaging with diffusionweighted imaging (WB-MRI with DWI) is a radiation-free method which allows imaging of the body with excellent soft tissue contrast in a single examination and could therefore be an attractive alternative to FDG-PET/CT for the staging of HL in children [15][16][17][18]. With the addition of DWI to the WB-MRI protocols, it is suggested that not only anatomical but functional information is provided as well, offering a possible surrogate to the functional information provided with FDG-PET/ CT [19].…”
Section: Introductionmentioning
confidence: 99%
“…В других опубликованных работах число пациентов в исследуемых группах было сравнительно небольшим -от 15 до 68 человек. Чувствительность диагностики поражения ЛУ при МРТ-ДВИ составила 90-98%, специфичность -94-99%, органов -79-100 и 99-100% соответственно [8][9][10][11], что соответствует полученным нами данным. Лишь в одной из указанных работ учитывали поражение неувеличенных ЛУ [11].…”
Section: Discussionunclassified
“…Еще одной особенностью большинства опубликованных работ является оценка возможностей МРТ-ДВИ по отношению к стандарту диагностики, в качестве которого использовали ПЭТ/КТ. В единичных публикациях в качестве стандарта применяли комплекс методов диагностики (включая ПЭТ/КТ), биопсию и наблюдение в динамике [10,11]. По нашему мнению, такой стандарт более обоснован, поскольку при ПЭТ/КТ возможны как ложноположительные, так и ложноотрицательные результаты.…”
Section: Discussionunclassified
See 1 more Smart Citation